1999
DOI: 10.1254/jjp.79.359
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic Peptide Receptors, NPR-A and NPR-B, in Cultured Rabbit Retinal Pigment Epithelium Cells

Abstract: We tried to detect natriuretic peptide (NP) receptor (NPR-A and NPR-B) mRNAs in cultured rabbit retinal pigment epithelium (RPE) cells and examined the regulation of their expression in relation to subretinal fluid absorption or RPE cell proliferation. RPE cells from 2-4 passages were grown to confluence on microporous membranes and analyzed for levels of expression of receptor mRNAs by quantitative RT-PCR and Northern blotting. The expression of NPR-B mRNA was approximately tenfold higher than that of NPR-A m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…ANP blocks the VEGF response, if given apically but not basolaterally, which indicates an apical localization of ANP receptors in the RPE cells. Previous studies have shown that NP receptors are present in the retina 13 and in RPE cells 24 ; however, direct evidence for exact localization of the receptors in the retina or RPE cells does not exist.…”
Section: Discussionmentioning
confidence: 94%
“…ANP blocks the VEGF response, if given apically but not basolaterally, which indicates an apical localization of ANP receptors in the RPE cells. Previous studies have shown that NP receptors are present in the retina 13 and in RPE cells 24 ; however, direct evidence for exact localization of the receptors in the retina or RPE cells does not exist.…”
Section: Discussionmentioning
confidence: 94%
“…Also in the RPE cell layer of the human retina strong ANP immunolabeling has previously been shown [26] . In addition, mRNA of NPR-A and NPR-B, both ANP receptors, has been demonstrated in cultured rabbit RPE cells [9] . Histochemical and molecular cloning studies have also revealed the presence of the NPR-A and NPR-B in the human and turtle retina [7,10,24] .…”
Section: Discussionmentioning
confidence: 99%
“…In the eye, studies have shown that NP receptors are present in the mammalian neural retina (Rollin et al, 2004) and RPE (Fujiseki et al, 1999), and the activation of these receptors can influence vascular endothelial growth factor-induced permeability changes in the RPE (Ablonczy and Crosson, 2007;LaraCastillo et al, 2009). However, the receptor subtype responsible for this response has not been investigated.…”
Section: Discussionmentioning
confidence: 99%